Evaluating changes in the breast cancer-related quality of life of young women with breast cancer: long-term results from a multicenter prospective cohort - Bryan F. Vaca-Cartagena; Fernanda Mesa-Chavez; Ana S. Ferrigno Guajardo; Hatem A. Azim; Federico Rotolo; Alejandra Platas; Alan Fonseca; Marlid Cruz-Ramos; Ana Rodriguez; Alejandro Mohar; Cynthia Villarreal-Garza (Therapeutic Advances in Medical Oncology)
Background: Young women with breast cancer (YWBC) typically undergo intensive treatment that negatively impacts their quality of life (QoL). However, limited information is available on how their QoL changes, as most research has focused on older patients. Objectives: To assess changes in QoL among YWBC, identify the most affected QoL domains, and identify the factors associated with these changes. Design: Joven & Fuerte is a multicenter cohort of women aged ⩽40 in Mexico with newly diagnosed BC from 2014 to 2020. Methods: Participants completed the European Organization for Research and Treatment of Cancer Breast Cancer module QLQ-BR23 questionnaire at five different time points from enrollment until year 5 postdiagnosis. Clinical and treatment data were also collected. Group-based multivariate trajectory modeling was used to analyze longitudinal changes across QoL domains and classify patients into appropriate groups. Logistic models were then employed to identify associations between variables and group classification. Results: A total of 477 women (median age: 36 years; interquartile range 32–38) were included. Most had public health insurance (87%) and were diagnosed with stage II (49%) or III (39%) BC. Two trajectory groups, namely, “good” and “poor,” were identified based on QLQ-BR23 scores. Most patients ( n  = 294, 62%) were in the poor group. In the good group, sexual enjoyment scores remained stable from baseline to year 5 (51.4), whereas those in the poor group decreased (51.0–37.3). Distress related to hair loss over time declined, with scores decreasing from 36.3 to 27.0 in the good trajectory group and from 43.4 to 31.2 in the poor trajectory group. For future perspective, the good group improved from 56.4 to 79.0, while the poor group increased from 39.3 to 57.2. Patients with human epidermal growth factor receptor 2-positive BC (adjusted odds ratio (aOR) = 0.57, 95% confidence interval (CI) 0.35–0.94, p  = 0.028) and those with public health insurance (aOR = 0.41, 95% CI 0.16–0.90, p  = 0.035) were less likely to belong to the poor trajectory group. Conclusion: A high proportion of YWBC experience a poor QoL trajectory over time, particularly in areas related to sexual health, future perspective, and hair loss.